Impact of rivaroxaban on point-of-care assays. Issue 153 (May 2017) - Fontana, Pierre; Alberio, Lorenzo; Angelillo-Scherrer, Anne; Asmis, Lars M.; Korte, Wolfgang; Mendez, Adriana; Schmid, Pirmin; Stricker, Hans; Studt, Jan-Dirk; Tsakiris, Dimitrios A.; Wuillemin, Walter A.; Nagler, Michael
Abstract: Background: Point-of-care testing (POCT) is regularly used to assess haemostasis in various clinical settings. The impact of rivaroxaban on those POCT is still elusive. We aimed to study the effects of rivaroxaban on most commonly used POCT assays. Methods: Blood samples were taken before, 3 h, and 24 h after administration of 20 mg rivaroxaban to 20 healthy volunteers as part of a prospective, multicenter validation study (clinicaltrials.gov NCT01710267 ). Blood samples were analysed with thromboelastometry (ROTEM®), two platelet function assays (INNOVANCE® PFA-200 and Multiplate®), and the CoaguChek® XS. Rivaroxaban plasma levels were determined using liquid chromatography-mass spectrometry. Results: Rivaroxaban significantly modified some thromboelastometry parameters (CT INTEM: mean difference 56.1 s, 95% CI: 41.8, 70.3; CT EXTEM: 47.5 s, 95% CI: 37.8, 57.1; CT HEPTEM: 50.1 s, 95% CI: 34.7, 65.6), and CoaguChek® XS parameters (prothrombin time: mean difference 3.8 s, 95% CI: 3.3, 4.2; INR: 0.32, 95% CI: 0.27, 0.38; prothrombin ratio: − 36.1%, 95% CI: − 32.3, − 39.9). CT EXTEM and INR showed a moderate correlation with rivaroxaban plasma levels (r = 0.83; 95% CI 0.69, 0.9 and r = 0.83; 95% CI 0.70, 0.91, respectively) and a high sensitivity to detect rivaroxaban treatment at peak levels (0.95; 95% CI: 0.76, 1.0 and 0.90, 95% CI 0.70, 0.99, respectively). Conclusions: Rivaroxaban 20 mg treatment significantly alters ROTEM® and CoaguChek® XS parameters. Even though POCT do not allow precise quantification of rivaroxaban plasma concentration, CT EXTEM and CoaguChek XS detect the presence of rivaroxaban at peak level with a high sensitivity. Highlights: Rivaroxaban significantly affects thromboelastometry and capillary PT measurements. CT EXTEM and capillary INR are sensitive to detect rivaroxaban at peak levels. Studied POCT cannot quantify rivaroxaban concentration precisely.